Role of BAG3 in bovine Deltapapillomavirus‐mediated autophagy. Issue 1 (10th December 2021) - Roperto, Sante
Abstract: Bovine Deltapapillomavirus genus (δPV), comprises four members that are highly pathogenic and are frequently associated with bladder tumors of adult cattle and water buffaloes. In particular, bovine δPV‐2 and δPV‐13 are commonly found in urinary bladder tumors in adult large ruminants reared fully or partially on hilly/mountain pasturelands rich in bracken fern ( Pteridium spp.) as the urinary bladder of the herbivores is the specific target for bracken genotoxins such as ptaquiloside (PT). PT is a sesquiterpenoid responsible for alkylation of adenine of codon 61 of gene H‐Ras, which results in Glutamine 61 substitution that is essential for guanosine triphosphate (GTP) hydrolysis. Glutamine substitution at position 61 impairs the intrinsic GTPase activity. Therefore, active GTP‐bound conformations (Ras‐GTP) accumulate in cells, thereby causing abnormal cell proliferation and differentiation. The aim of the present study is to stress how bovine δPVs upregulate different forms of selective autophagy, of which BAG3 is a key player. BAG3 plays a central role in autophagy and acts as a multifunctional hub for an interaction network at the cytosolic and mitochondrial level. BAG3 is a functional partner of bovine δPV E5 oncoprotein and forms a complex with molecular chaperones Hsc70/Hsp70/Hsp8B and with cochaperone CHIP. BAG3 interacts with Synpo2. It is believed that this interaction has a crucial role for autophagosome (mitophagosome) formation. Furthermore, in urothelial cells infected by bovine δPVs, BAG3 interacts with parkin and some receptors such as BNIP3/FUNDC1, which suggests that BAG3 is involved in both parkin‐dependent and ‐independent mitophagy that appear upregulate in bladder carcinogenesis of cattle induced by bovine δPVs. Surprisingly, BAG3 interacts also with ERAS, a protein encoded by the ERas gene, a novel member of the RAS family. Unlike in humans, the ERas gene is a functional gene in the cells of adult cattle, and it appears to play a role in bovine BAG3‐mediated selective autophagy, including mitophagy observed in urothelial cells spontaneously infected with bovine papillomavirus.